2020
DOI: 10.3390/s20072115
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Condition Monitoring Method for Gearboxes Operating in Impulsive Environments

Abstract: Reliable condition indicators are necessary to perform effective diagnosis and prognosis. However, the vibration signals are often corrupted with non-Gaussian noise and rotating machines may operate under time-varying operating conditions. This impedes the application of conventional condition indicators. The synchronous average of the squared envelope is a relatively simple yet effective method to perform fault detection, fault identification and fault trending under constant and time-varying operating condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…The proposed technique was applied to a simulated signal as well as a real signal. S. Schmidt et al [15] suggested the synchronous median of the square of the envelope method, instead of the synchronous mean of the square of the envelope of a vibration signal, for fault diagnosis of gearboxes operating under variable conditions and in an impulsive environment. This study showed its effectiveness on simulated and real signals.…”
Section: Of 22mentioning
confidence: 99%
“…The proposed technique was applied to a simulated signal as well as a real signal. S. Schmidt et al [15] suggested the synchronous median of the square of the envelope method, instead of the synchronous mean of the square of the envelope of a vibration signal, for fault diagnosis of gearboxes operating under variable conditions and in an impulsive environment. This study showed its effectiveness on simulated and real signals.…”
Section: Of 22mentioning
confidence: 99%
“…The results which are obtained by means of various measurements can be processed by dedicated software FLIR Tools [13]. Studies on the development of longwall conveyors are presented in works [14][15][16][17][18][19][20][21][22]-they are part of the innovative development of machinery and equipment [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…An impulsive noise in signal processing procedures developed for local damage detection has been recognized as a critical challenge [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. It is well known that faulty bearings produce a cyclic impulsive signal and the properties of the Signal of Interest depend on the bearing geometry, rotational speed, and fault size.…”
Section: Introductionmentioning
confidence: 99%